Manifestations of Bureaucratic Reform through the Electronic Service Manuscript System: A SWOT Analysis at the Directorate General of Vocational Education - Apriyani, Nur; Jannah, Lina Miftahul (Universitas Muhammadiyah Yogyakarta, 2022)
The Indonesian government continues to optimize the use of information technology in realizing the implementation of electronic-based government (e-government). The development of electronic service scripts in various government agencies is one manifestation of bureaucratic reform. This study aims to evaluate the application of the Electronic Service Manuscript System (SINDE) at the Directorate General of Vocational Education, Ministry of Education, Culture, Research, and Technology using SWOT analysis. The study used a descriptive quantitative method by distributing questionnaires to 43 respondents from several work units within the Directorate General of Vocational Education. The analysis is based on the Internal Factors Strategic (IFAS) matrix which describes the factors of strength and weakness and the External Factors Strategic (EFAS) matrix which describes the opportunities and threats factors. These results indicate that the weight of the strength dimension score is 1.97, the weight dimension of the weakness dimension is 1.63, the opportunity dimension score is 1.92, and the threat dimension score is 1.52. The total value of the average score on the IFAS matrix is 3.61 and the total value of the average score on the EFAS matrix is 3.44 which puts that the application of SINDE is in Quadrant I where it has great strength and opportunity.